2002
DOI: 10.1007/s00468-002-0206-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient partitioning and storage in arid-zone forests of the mangroves Rhizophora stylosa and Avicennia marina

Abstract: Mangrove partitioning and storage of macronutrients and trace metals were examined in different arid coastal settings of Western Australia. Total living biomass in three Rhizophora stylosa forests, which ranged from 233 to 289 t DW ha -1 , was significantly greater than biomass in three Avicennia marina forests (range: 79-155 t DW ha -1 ). Although prop roots and stems were the largest single tree components for R. stylosa and A. marina, respectively, most nutrients were stored in leaves and living roots of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
56
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 26 publications
14
56
4
2
Order By: Relevance
“…Our values for root biomass and total sediment N stocks (15.4 ± 1.0 t N ha −1 ) are comparable with tropical A. marina growing in northern Australia (root biomass composed of 0.45-0.75% N, ∼0.08-0.3 t N ha −1 stored in root biomass, Table 4; Alongi et al, 2003). Our total sediment N stocks are also comparable with other tropical mangrove forests (Fujimoto et al, 1999;Ramos e Silva et al, 2007), yet higher than temperate K. obovata sediment in Japan (Khan et al, 2007; Table 4).…”
Section: Total Ecosystem Carbon and Nitrogen Stocks In Temperate A Msupporting
confidence: 79%
See 1 more Smart Citation
“…Our values for root biomass and total sediment N stocks (15.4 ± 1.0 t N ha −1 ) are comparable with tropical A. marina growing in northern Australia (root biomass composed of 0.45-0.75% N, ∼0.08-0.3 t N ha −1 stored in root biomass, Table 4; Alongi et al, 2003). Our total sediment N stocks are also comparable with other tropical mangrove forests (Fujimoto et al, 1999;Ramos e Silva et al, 2007), yet higher than temperate K. obovata sediment in Japan (Khan et al, 2007; Table 4).…”
Section: Total Ecosystem Carbon and Nitrogen Stocks In Temperate A Msupporting
confidence: 79%
“…The total amount of C stored in above and below-ground biomass plus sediment was 117.1 ± 16.8 t C ha −1 . These values are within the range observed in other temperate mangrove systems (Howe et al, 2009;Saintilan et al, 2013), yet lower than those values reported from tropical mangrove forests (Table 4; Fujimoto et al, 1999;Alongi et al, 2003;Chmura et al, 2003). Lower C stocks in temperate mangrove forest are predominantly a result of lower mangrove biomass (as described above), as well as lower sediment C stocks.…”
Section: Total Ecosystem Carbon and Nitrogen Stocks In Temperate A Msupporting
confidence: 79%
“…In general the concentrations of the heavy metals (Fe, Mn, Cu, and Zn) appear to be within the lower range of concentrations reported for other mangrove sites in Brazil (Machado et al, 2002;Bernini et al, 2010) and elsewhere (Alongi et al, 2003;MacFarlane et al, 2007). The δ 13 C values separated S. densiflora from the rest because of its C4 photosynthesis.…”
Section: Plantssupporting
confidence: 61%
“…Sulfur concentrations are well below concentrations reported for Avicennia and Rhizophora species elsewhere (Fry and Smith III 2002;Alongi et al, 2003;Bernini et al, 2006;Medina et al, 2010). We do not have an explanation for this fact but hypothesize that the mesic, humid climate where these communities are growing, reduces the stress of high level of available sulfate from marine waters through leaching brought about by rain and superficial run-off.…”
Section: Plantscontrasting
confidence: 53%
See 1 more Smart Citation